Land space simulation of urban agglomerations from the perspective of the symbiosis of urban development and ecological protection: A case study of Changsha-Zhuzhou-Xiangtan urban agglomeration - Jingzhi Li (Elsevier, 2021)
Simulation of future land space changes in urban agglomerations is a powerful means to optimize regional spatial structure and improve human well-being. This study highlights the equilibrium between urban development and ecological protection and introduces ecological impact coefficient and land use protection coefficient to measure the degree of sustainable land development. The system dynamic model was used to simulate the dynamics of urban development space, ecological space, and urban agricultural space in the Changsha-Zhuzhou-Xiangtan urban agglomeration from 2019 to 2035. Four development scenarios were used in the simulation, namely, status-quo, economic-centric, environment-centric, and coordinated equilibrium. Simulation results show that for the year 2035, urban development space scale would increase by 678.91 km2 under the status quo, increase by 870.12 km2 under the economic-centric scenario, increase by 740.98 km2 under an environment-centric setting, and increase by 775.54 km2 with coordinated equilibrium. The various scenarios would have significant differences in ecological impact and land use protection coefficients, with the environment-centric scenario yielding the highest values for these indicators. The approach presented in this study shows that the needs for urban development can be achieved while also protecting ecological and urban agricultural spaces and that allocation of production, living, and ecological spaces can be optimized using multi-scenario simulation. The development of ecological impact coefficients and land use protection coefficients, as well as the use of different development scenarios, can be used as reference for the more efficient use of land resources areas and the formulation of land-use and spatial planning.